STRATEGY FOR COLLABORATION IN SMALL MEDIUM ENTERPRISES: A FRAMEWORK FOR STRATEGIC PARTNERSHIP (A CASE STUDY IN FASHION INDUSTRY) - Violanda Thahira, Asyifa
Majority of firms in Indonesia are categorized as Small-Medium Enterprises. SME is an essential role in Indonesia's economic development. SMEs create jobs opportunity to support in scaling down the unemployment issue. Thus, SME should be able to innovate their product or service on facing the globalization challenge aim to reinforce the brand's strength of SMEs itself and to accomplish in competing with international products or services which are deluging Indonesia's market. No company grows only on its own. Aside from they used their resources, some SME also needs the external resources too to help them in acquiring the innovation. The innovation that SMEs do in competing in global markets can be done through collaboration. To enhance the company, forming a collaborative partnership will empower the company to deliver projects which may not be done by solo. Collaboration is one of the forms of innovation activities that support a company to emerge the market and increase business performance. However, SMEs still face uncertainty ways to accomplish it. The search capabilities and networks are SMEs' challenges to identify the potential partners of collaboration. But, it does not mean SMEs have no ability to accomplished beneficial collaboration. This research aims to understand the effective and beneficial collaboration in inspiring and creating strategy development for fashion SMEs by identifying the collaboration strategies applied in its company. From those strategies, the researcher proposes the best recommendation that can be implemented in the own researcher company, LOOKOUT to create a beneficial collaboration. This research used a qualitative approach with an in-depth interview method conducted with purposive sampling. Thus, the respondents of this research consist of several criteria. There were five main elements of collaboration the researcher used to gain the result. Those are, the company vision of the collaboration, the requirements in the partner selection process, the collaboration form which focused on partnership form, the process and structure of a collaborative organization, and the last is about the review of the company after implementing the collaboration. Based on the research, each company’s collaboration strategy gave varied results. The result also shows that collaboration affects the improvement of the company's business performance in the aspect of brand awareness and profit. According to the result, the best recommendation for the LOOKOUT company regarding partner selection is about each member has to increase the networking to leverage the business relation. It is to support the company to have a higher chance of getting the potential partner. LOOKOUT also has to find a collaboration partner suitable with its company's capability to avoid the bad result of collaboration. For the process of collaborative organization aspect, sometimes a company is necessary to register their brand to intellectual property to keep the brand away from a legal problem.